Amyloid and Related Disorders Surgical Pathology and Clinical Correlations / edited by Maria M. Picken, Guillermo A. Herrera, Ahmet Dogan. - Picken, Maria M.; Picken, Maria M.; Herrera, Guillermo A.; Herrera, Guillermo A.; Dogan, Ahmet.; Dogan, Ahmet. (Current Clinical Pathology, 2015)
The second edition of this text presents an overview of the most recent developments in this area including clinical presentation, etiology, pathogenesis, and differential diagnosis. The rationale for various therapies, including transplantation, is discussed and tissue diagnosis (its pitfalls and strategies for avoiding them) and laboratory support are included. The involvement of all major organ systems including renal/genitourinary, cardiac, gastrointestinal, pulmonary, peripheral nerve/central nervous system, soft tissue, skin, lymph node/spleen and bone marrow pathology is also covered. Amyloid and Related Disorders, Second Edition will be invaluable to specialized and general pathologists as well as cytopathologists. Other medical professionals may also benefit from this concise update on the systemic amyloidoses.